HUBUNGAN ANTARA KADAR GULA DARAH BAYI BARU LAHIR DENGAN IBU HAMIL YANG MENGALAMI OBESITAS - Rumangkang, Bella; Wilar, Rocky; Pateda, Vivekenanda (Universitas Sam Ratulangi, 2016)
Abstract: Nowadays, obesity has gotten serious concerns because of the increasing number of sufferers including the number of obese people in pregnant women. The number of obese pregnant women has increased by approximately 18.5% to 38.3%. Obesity is a condition that indicates an imbalance between the height and the weight due to the fat tissue in the body resulting in weight excess beyond the ideal weight. The obesity is nearly always harmful to the mother and fetus, and it can come down to the infants. While in the womb, the fetus receives all the energy and glucose which are obtained from the mother. After the birth, the amount of glucose, that is stored in the baby's body in the form of liver and muscle glycogen, is only enough to supply the needs of the baby for a few hours, so the baby's blood sugar levels decreases and hypoglycemic occurs.Objectives: This research intends to determine correlation between the blood sugar levels of newborn babies and pregnant women who experience obesity.Material Methods: This research is a prospective analytical study conducted in pregnant women through direct data collection by measuring the weight and height, and the measurement of the blood sugar levels in the newborn babies in RSUP Prof. Dr. R. D Kandou Manado, RS R.W Monginsidi Teling Manado, RSU Pancaran Kasih Manado, and Puskesmas Bahu Manado during the months of November 2015 to January 2016.Result: The study result of the 38 respondents found out that pregnant women who are obese to the obese category I as many as 30 people (78.9%), 5 people (13.2%) in obese II , and 3 people (7.9%) in obese III. The distribution according to the frequency of food consumption of mothers in which 36 of them (94.7%) with a frequency of ≥ 3x meals a day and 2 (5.3%) with a food frequency ≤ 3 times a day. The distribution according to the activity of the mother that the majority of mild activity as many as 31 people (81.6%), 4 people (10.5%) having tough activities, and 3 people (7.9%) having light activities. The distribution according to the mother's knowledge about obesity there were 14 people (36.8%) who knew about obesity and there were 24 people (63.2%) who did not know about obesity. According to the mother's knowledge on maternal blood sugar, they all (100%) knew. Based on the distribution according to the sex of a newborn babies, there were 23 male infants (60.5%) and 15 female infants (39.5%). According to the baby's weight distribution; there were 14 infants (36.8%) with a body weight between 3100 to 3500 grams, 13 infants (34.2%) with a body weight between 2,500 to 3,000 grams, and 11 infants (29%) by weight between 3600 to 4000 grams. The distribution according to the blood sugar levels that the majority of newborn infants with low blood sugar levels were between 15-20 mg / dL totaling 21 infants (55.3%), blood sugar levels between 26-30 mg / dL were 9 infants (23.7 %), while blood sugar levels between 21-25 mg / dL and 36-40 mg / dL obtained a similar number that is 4 infants (10.5%).Conclusion: The research result which was done has two different conclusions. Based on the theory, there was H1 which has relationship between all pregnant women who are obese and low blood sugar levels in the newborn babies. Based on the statistical test, there was H0 which has no significant correlation between blood sugar levels of newborn babies and mothers who are obese.Keywords: obesity, pregnant women, blood sugar levels, newborn babies, hypoglycemia.Abstrak: Saat ini obesitas mendapat perhatian yang serius karena jumlah penderitanya yang semakin meningkat termasuk jumlah penderita obesitas pada ibu hamil. Jumlah penderita obesitas pada ibu hamil meningkat sekitar 18,5% sampai dengan 38,3%. Obesitas merupakan keadaan yang menunjukkan ketidakseimbangan antara tinggi dan berat badan akibat jaringan lemak dalam tubuh sehingga terjadi kelebihan berat badan yang melampaui berat badan ideal. Obesitas hampir selalu berbahaya bagi ibu dan janinnya, dan dapat menurun pada bayi. Selama dalam kandungan, janin memperoleh semua energi dan glukosa yang didapat dari ibu. Setelah kelahiran, jumlah glukosa yang disimpan dalam tubuh bayi dalam bentuk glikogen hati dan otot hanya cukup untuk menyuplai kebutuhan bayi beberapa jam saja, sehingga kadar gula darah bayi menurun dan terjadi hipoglikemia.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara kadar gula darah bayi baru lahir dengan ibu hamil yang mengalami obeistas.Metode Penelitian: Penelitian ini merupakan studi analitik prospektif yang dilakukan pada ibu hamil melalui pengambilan data secara langsung dengan pengukuran berat badan dan tinggi badan dan pengukuran kadar gula darah pada bayi baru lahir di RSUP Prof. Dr. R. D Kandou Manado, RS R.W Monginsidi Teling Manado, RSU Pancaran Kasih Manado, dan Puskesmas Bahu Manado selama bulan November sampai Januari 2016.Hasil: Hasil peneilitian dari 38 responden di dapatkan ibu hamil yang mengalami obesitas dengan kategori obese I sebanyak 30 orang (78,9%), obese II sebanyak 5 orang (13,2%), dan obese III sebanyak 3 orang (7,9%). Distribusi menurut frekuensi konsumsi makanan dari ibu diperoleh 36 orang (94,7%) dengan frekuensi makanan ≥ 3x sehari dan 2 orang (5,3%) dengan frekuensi makanan ≤ 3x sehari. Distribusi menurut aktivitas ibu bahwa mayoritas beraktivitas ringan sebanyak 31 orang (81,6%), aktivitas berat didapatkan 4 orang (10,5%) dan aktivitas ringan didapatkan 3 orang (7,9%). Distribusi menurut pengetahuan ibu tentang obesitas terdapat 14 orang (36,8%) yang mengetahui tentang obesitas dan terdapat 24 orang (63,2%) yang tidak mengetahui tentang obesitas. Menurut pengetahuan ibu tentang gula darah didapatkan semua ibu (100%) mengetahuinya. Berdasarkan distribusi menurut jenis kelamin bayi baru lahir didapatkan laki-laki berjumlah 23 bayi (60,5%) dan perempuan berjumlah 15 bayi (39,5%). Distribusi menurut berat badan bayi didapatkan 14 bayi (36,8%) dengan berat badan antara 3100 sampai 3500 gram, 13 bayi (34,2%) dengan berat badan antara 2500 sampai 3000 gram, dan 11 bayi (29%) dengan berat badan antara 3600 sampai 4000 gram. Distribusi menurut kadar gula darah bayi baru lahir bahwa mayoritas bayi dengan kadar gula darah terendah antara 15 – 20 mg/dL berjumlah 21 bayi (55,3%), kadar gula darah antara 26 – 30 mg/dL berjumlah 9 bayi (23,7%), sedangkan kadar gula darah antara 21 – 25 mg/dL dan 36 – 40 mg/dL diperoleh jumlah yang serupa yaitu 4 bayi (10,5%).Simpulan: Dari hasil penelitian yang dilakukan diperoleh 2 simpulan yang berbeda. Berdasarkan teori, didapatkan H1 yaitu ada hubungan antara semua ibu hamil yang mengalami obesitas dengan kadar gula darah yang rendah pada bayi baru lahir. Berdasarkan uji statiska, didapatkan H0 yaitu tidak terdapat hubungan yang bermakna antara kadar gula darah bayi baru lahir dengan ibu yang mengalami obesitas.Kata kunci: obesitas, ibu hamil, kadar gula darah, bayi baru lahir, hipoglikemia.